Who gets a childhood?: race and juvenile justice in twentieth-century Texas - Bush, William S. (Politics and culture in the twentieth-century South, 2010)
Introduction : Race, childhood, and juvenile justice history -- The other lost generation : reform and resistance in the juvenile training schools, 1907-1929 -- Socializing delinquency : child welfare, mental health, and the critique of institutions, 1929-1949 -- Juvenile rehabilitation and the color line : the training school for Black delinquent girls, 1943-1950 -- James Dean and Jim Crow : the failure of reform and the racialization of delinquency in the 1950s -- "Hard to reach" : the politics of delinquency prevention in postwar Houston -- Circling the wagons : the struggle over the Texas Youth Council, 1965-1971 -- Creating a right to treatment : Morales v. Turman, 1971-1988 -- Epilogue : The new American dilemma